Identification in Cognitive Maps in Impulse Process Mode with Incomplete Measurement of Nodes Coordinates - Miliavskyi, Yu.L. (Кибернетика и вычислительная техника, 2019)
The purpose of the article is to research and develop a method for identifying weights of cognitive map nodes in case when number of nodes is known, but not all of them are measured. Results. Identification method based on 4SID method is suggested. It allows finding some realization of the system equivalent to the original cognitive map in its outputs, with the control observation matrices remaining unchanged. Invariants of the original and identified systems are analyzed. Practical example of identifying a cognitive map of an IT company is considered. It is shown what the accuracy of the suggested method depends on and under which conditions it is applicable.